2021
DOI: 10.3389/fnins.2021.629478
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and Functional Brain Connectivity Differentiates Chess Masters From Amateur Players

Abstract: A common task in brain image analysis includes diagnosis of a certain medical condition wherein groups of healthy controls and diseased subjects are analyzed and compared. On the other hand, for two groups of healthy participants with different proficiency in a certain skill, a distinctive analysis of the brain function remains a challenging problem. In this study, we develop new computational tools to explore the functional and anatomical differences that could exist between the brain of healthy individuals i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Raw neural signals were band pass filtered at 250 Hz – 3 kHz using a 1st order Butterworth filter in MATLAB (MathWorks, Natick, MA). Even though, recent work has shown that there is valuable information in high frequency signals ( RaviPrakash et al, 2021 ), band-pass filtering, as the one used herein, has been a commonly used technique for spike sorting ( Quiroga, 2012 ). Spike sorting analysis was performed using Offline Sorter (V3, Plexon Inc. Dallas, TX).…”
Section: Methodsmentioning
confidence: 99%
“…Raw neural signals were band pass filtered at 250 Hz – 3 kHz using a 1st order Butterworth filter in MATLAB (MathWorks, Natick, MA). Even though, recent work has shown that there is valuable information in high frequency signals ( RaviPrakash et al, 2021 ), band-pass filtering, as the one used herein, has been a commonly used technique for spike sorting ( Quiroga, 2012 ). Spike sorting analysis was performed using Offline Sorter (V3, Plexon Inc. Dallas, TX).…”
Section: Methodsmentioning
confidence: 99%
“…The most accurate model KSVC selects the regions Frontal Sup Orb L and Cerebelum Crus2 R as the most important region, whereas none of the other methods identify Frontal Sup Orb L among the most important five regions. As there were very few results on this type of problem and even in a different setting so having a comparison is not possible [15,27].…”
Section: Comparison Of Results For Accuracy and Inferencementioning
confidence: 99%
“…[14] implemented several classification techniques to classify autistic and healthy patients and concluded that the neural networks outperformed other methods. [15] utilized the MRI scans of chess masters and novices to estimate morphometric connectivity. The authors introduced a novel functional morphometric similarity connectome by integrating functional and anatomical features, followed by classification using the SVM model after the feature selection technique is implemented.…”
Section: Introductionmentioning
confidence: 99%